SYMBOLIC BLOCK DECOMPOSITION IN HEXAHEDRAL MESH GENERATION - Adamek, Andrzej; Głut, Barbara (Computer Science, 2013)
Hexahedral mesh generation for three-dimensional solid objects is often done in stages. Usually an object is ﬁrst subdivided into simple-shaped subregions, which then are ﬁlled withhexahedral ﬁnite elements. This article presents an automatic subdividing method of polyhedron with planar faces. The subdivision is based on medial surface, axes and nodes of a solid.The main emphasis is put on creating a topology of subregions. Obtaining such a topologyinvolves deﬁning a graph structure OMG which contains necessary information about medialsurface topology and object topology, followed by simple symbolic processing on it.